Recent Advancements in the Architecting Schemes of Zinc Oxide-Based Photocatalytic Assemblies. Issue 4 (2nd October 2018) - Din, Muhammad Imran; Najeeb, Jawayria; Ahmad, Ghazia
Abstract : In recent times, leakage of the organic pollutants into water reserves because of the uncontrolled and ill-planned industrial development was regarded as one of the most fundamental worldwide concerns. The hazardous and deleterious effects associated with these pollutants demand the invention of effective degradation methodologies, which could be industrially employed prior to the discharge of industrial effluent into the aqueous environment. Various removal methods have been explored from the perspective of addressing this issue. The nanoparticles-(NPs) mediated photocatalytic degradation is one of such approaches which has attracted attention. Recently, the use of Zinc oxide (ZnO) NPs as heterogeneous photocatalysts has been under much review due to the improvements that have been presented for enhancing its catalytic efficacy and inhibiting photo-corrosion problems. Hence, a critical analysis summarizing and discussing these recent advances on ZnO NPs modification is needed. In this study, the descriptions of (1) stabilization mediums for NPs into producing more suitable and appropriate supports, (2) the revision of the architecting routes for ZnO NPs, (3) the introduction of various sorts of metal doping for enhancing the electron transduction capabilities of ZnO NPs and (4) the development of bi/polymetallic assemblies for combining the most-suited features of different metals in a single catalytic system are discussed. This article presents a comprehensive overview of the latest modifications achieved for the nanoassemblies of ZnO NPs employed for the light-mediated decomposition of organic pollutants.